Percutaneous closure of residual shunting in a patient with a fenestrated atrial septal defect occluder: A case report. Issue 31 (August 2018) - Man, Wang; Xinxin, Ma; Yueli, Zhang; Feng, Li
Abstract: Rationale: Fenestrated atrial septal defect (ASD) occlusion has been performed in patients complicated with severe pulmonary hypertension (PH). Nevertheless, the persistent interatrial residual shunting in the fenestration might increase the risk of paradoxical embolism. Percutaneous closure of fenestrated ASD occluder (ASO) has not yet been reported. Patient concerns: A 26-year-old patient with a 25-mm ASD and severe PH underwent ASD closure using a Memory ASO with a waist of 32 and 6-mm custom-made fenestration. Echocardiography revealed the fenestration remained 6 mm and the pulmonary artery pressure decreased to the normal range at the 6-month follow-up. Diagnoses: Persistent interatrial residual shunting in ASO. Interventions: Percutaneous closure of residual interatrial shunting was performed using a waist of 8-mm ASO under guidance of TEE. Outcomes: The fenestration was successfully closed. Neither thromboembolism nor infection events were noted during the 12-month follow-up after the procedure. Lessons: This case illustrates that percutaneous closure of the residual shunting in fenestrated ASO was feasible and safe for short- and long-term.